1992
DOI: 10.1093/jnci/84.19.1500
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Incidence and Survival Among American Indians Registered for Indian Health Service Care in Montana, 1982-1987

Abstract: We conclude that it is feasible to develop state-specific cancer incidence and survival estimates for American Indians in at least some states in different regions of the United States. Collaboration between the IHS and a state tumor registry is likely to improve the case ascertainment achieved by either agency alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…[4][5][6][7][8][9][10][11]14,[18][19][20][21][22][23][24][25][26][27][28][29] The results illustrate the variation in morbidity and mortality observed among different American Indian and Alaska Native populations studied to date. No populationbased study has described cancer incidence in these populations with more than a regional scope.…”
Section: Bakgroundmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11]14,[18][19][20][21][22][23][24][25][26][27][28][29] The results illustrate the variation in morbidity and mortality observed among different American Indian and Alaska Native populations studied to date. No populationbased study has described cancer incidence in these populations with more than a regional scope.…”
Section: Bakgroundmentioning
confidence: 99%
“…Malignant neoplasm survival rates for American Indian populations have been shown to be lower then the general population 4–7. Young et al found lower cancer survival among American Indians in the SEER program from 1973 to 1979 7.…”
Section: Discussionmentioning
confidence: 99%
“…The 1989–91 age‐adjusted malignant neoplasm mortality rate among American Indians in Montana and Wyoming was higher than that of U.S. All Races rate1 even though previous studies in various populations of American Indians have indicated a lower overall incidence of malignant neoplasms 2, 3. Previous studies also have indicated a lower survival rate among native populations 4–7. The study by Bleed et al indicated a significantly poorer survival rate among Montana American Indians when compared with U.S. whites 4.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Studies examining cancer incidence patterns among American Indians (AIs) have generally been limited to data for restricted time intervals and/or have been restricted to selected geographic regions which either have a large numbers of AIs and/or a population‐based cancer registry 1–9 …”
mentioning
confidence: 99%